Mediating Effects of Organizational Commitment and Perceived Organizational Support on HRM Practices and Turnover Intention: A Study of Private Universities in Bangladesh - Raihan, Joarder Mohd Hasanur (2012)
Excessive employee turnover is detrimental to any organization. High rate of faculty turnover especially in the private universities has become one of the most pressing issues for higher educational institutions in Bangladesh. The main objective of this study was to empirically determine the significant human resource management(HRM) practices that influence the faculty turnover intention in the said context. Earlier study had suggested that employees’ positive perceptions of organizational human resource practices could lead to increased organizational commitment (OC) and perceived organizational support (POS), which in turn could negatively influence employees’ behavioral intention. The present study had explored the mediating role of OC and POS on the relationship between some HRM practices and faculty turnover intention. The study employed the survey method approach. The researcher had collected the survey data for statistical analysis to test the hypothesized relationships between the variables which were studied. The study had used a number of different statistical techniques such as factor analysis, correlation analysis, multiple regressions and hierarchical multiple regression for analyzing the data. The results of the study had provided the general support for the hypotheses. They revealed that gender and age were among the variables that had significantly and positively influenced the faculty turnover intention. Among the six independent variables, faculty job security, faculty compensation and faculty supervisory support were found to be significantly and negatively related to faculty turnover intention. In addition, they also confirmed that affective commitment, continuance commitment and perceived organizational support were significantly and negatively related to the faculty turnover intention. Furthermore, the results of the hierarchical multiple regression analyses also indicated that affective commitment, continuance commitment and perceived organizational support mediate the relationship between HRM practices and faculty turnover intention. Specifically, affective and continuance commitment partially mediate the relationship between faculty compensation, faculty supervisory support and faculty turnover intention relationship, while affective commitment fully mediates the faculty job security and faculty turnover intention relationship. Perceived organizational support fully mediates the relationship between HRM practices and faculty turnover intention. The empirical relationships between HRM practices, organizational commitment, perceived organizational support and faculty turnover intention suggested that it would be beneficial to the management of private universities to improve faculty turnover situation. Besides that, the contributions, the limitations and implications of the study were also discussed.